Non-albuminuric renal disease among subjects with advanced stages of chronic kidney failure related to type 2 diabetes mellitus. (March 2014) - Boronat, Mauro; García-Cantón, César; Quevedo, Virginia; Lorenzo, Dionisio L.; López-Ríos, Laura; Batista, Fátima; Riaño, Marta; Saavedra, Pedro; Checa, María D.
Abstract Urinary albumin excretion has been consistently found to be normal in a significant number of subjects with early stages of diabetic kidney disease. This study was aimed to estimate the prevalence and characteristics of non-albuminuric chronic kidney disease associated with type 2 diabetes mellitus among subjects who reach advanced stages of renal failure. Study population was composed of incident patients with advanced chronic kidney disease (glomerular filtration rate <30 mL/min) related to type 2 diabetes in a tertiary hospital from Gran Canaria (Spain) during a period of 2 years. Subjects were classified as normoalbuminuric (urinary albumin-to-creatine ratio [UACR] <30 mg/g), microalbuminuric (UACR ≥30 and <300 mg/g), or proteinuric (UACR ≥300 mg/g). Of 78 eligible patients, 21.8% had normoalbuminuria, 20.5% had microalbuminuria, and 57.7% had proteinuria. Individuals with normoalbuminuria were mostly women and had a lower prevalence of smoking and polyneuropathy than subjects with microalbuminuria or proteinuria. They also presented greater measures of body mass index and waist circumference, higher values of total and LDL cholesterol, and lower values of HbA1c and serum creatinine than subjects with microalbuminuria or proteinuria. Multivariate analysis demonstrated that female sex (positively) and HbA1c and polyneuropathy (negatively) were independently associated with absence of albuminuria. In conclusion, around 20% of subjects with diabetes-related advanced chronic kidney disease, characteristically women, have normal urinary albumin excretion. HbA1c and polyneuropathy are inversely related to this non-albuminuric form of nephropathy.